Phytochemical, HPLC Analysis and Antibacterial Activity of Crude Methanolic and Aqueous Extracts for Some Medicinal Plant Flowers. - Erian, N. S; Hamed, H. B; Farid, Mohammed; El-Khateeb, A. Y. (Arab Journal for Sciences and Research Publishing, 2016)
Methanolic and aqueous extracts of C. cardunculus, A. millefolium, C. officinalis, and M. chamomilla flowers were Phytochemical, Identification of polyphenols and flavonoids by HPLC, and also investigated for their antibacterial activity, Escherichia coli, Staphylococcus aureus and Bacillus subtillis. The phytochemical was observed that crude methanolic and aqueous extracts of investigated flowers the highest content from activity complex. HPLC analysis identified eighteen polyphenolic compounds as authentic samples namely: Gallic acid, pyrogallol, 4-amino benzoic, protocatechuic, cataehein, chlorogenic, catechol, e.picatechen, caffien, p.oh.benzoic, caffeic, vanillic, ferulic, ellagic, benzoic acid, salicylic acid, coumarin and cinnamic acid. While, flavonoid compounds its eleven compounds as authentic samples namely: narengin, rutin, hisperdin, romarinic, quereitrin, quereetrin, narenginin, kampferol, luteolin, hispertin, and 7-Hydoxyflavon. The methanolic extracts of C. officinalis and M. chamomilla flowers produced the highest growth inhibition (43.88 and 42.11%) for against B. subtillis at 6 mg/ml, While, the aqueous extracts of C. officinalis and M. chamomilla flowers produced the highest growth inhibition (29.99 and 29.22 %) for against Bacillus subtillis at 6 mg/ml. Moreover, the C. officinalis and C. cardunculus flowers extract produced the highest growth inhibition for methanolic and aqueous extracts of against Escherichia coli at 6 mg/ml.
Keywords: phytochemical; Hplc analysis; plant extracts; antibacterial activity